2018
DOI: 10.1016/j.mad.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA accumulation: A new hallmark of aging?

Abstract: Circular RNAs (circRNAs) are a newly appreciated class of RNAs found across phyla that are generated most commonly from back-splicing of protein-coding exons. Recent profiling of circRNAs genome-wide has shown that hundreds of circRNAs dramatically increase in expression during aging in the brains of multiple organisms. No other class of transcripts has been found to show such a strong correlation with aging as circRNAs-could they be playing a role in the aging process? Here, we discuss the different methods u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 74 publications
3
53
0
1
Order By: Relevance
“…The overall levels of tRNAs, rRNAs, and snoRNAs increase with age, whereas the levels of piRNAs decrease with age (Kato et al, ). circRNAs are a recently identified type of noncoding RNAs, whose ends are covalently linked and are implicated in transcriptional regulation (Knupp & Miura, ). A recent study indicated that the overall levels of circRNAs increase during C. elegans aging (Cortes‐Lopez et al, ).…”
Section: Age‐dependent Changesmentioning
confidence: 99%
“…The overall levels of tRNAs, rRNAs, and snoRNAs increase with age, whereas the levels of piRNAs decrease with age (Kato et al, ). circRNAs are a recently identified type of noncoding RNAs, whose ends are covalently linked and are implicated in transcriptional regulation (Knupp & Miura, ). A recent study indicated that the overall levels of circRNAs increase during C. elegans aging (Cortes‐Lopez et al, ).…”
Section: Age‐dependent Changesmentioning
confidence: 99%
“…In agreement with this hypothesis, agerelated modulation of microRNA levels in the rodent brain has been reported [46,47]. Notably, circular RNAs have been shown to accumulate in the aging brain [48], and long noncoding RNAs are also implicated in various aging processes [49]. Finally, although pluripotent cells and organoid culture methods have allowed to perform functional assays in human in vitro neural cell systems [50], mouse genetic models will remain essential for functional studies in vivo in the foreseeable future.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 77%
“…DGS(i, j) is the GIP kernel similarity between disease i and disease j. σ d is influential in tuning the kernel bandwidth calculated by the Eq. (5).…”
Section: ( )mentioning
confidence: 99%